Recent Trends in Private Activity in Infrastructure : What the Shift Away from Risk Means for Policy - Mästle, Clemencia Torres de; Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
In 2006, private participation in infrastructure continued its recovery for the third consecutive year from the steep downturn of the late 1990s. Activity was more evenly spread across all developing regions. However, it became more concentrated in less risky sub sectors, reflecting a lower appetite for risk among private investors. Greater selectivity has facilitated private sector's renewed interest, but it also raises questions about how governments can best tap private operators' abilities in high-need, high-risk areas such as water and electricity distribution. Recent projects in these areas indicate that the public sector together with the international financial institutions remains the main source of investment funding. As governments create arrangements to attract private participation, they also need to ensure an equitable distribution of benefits among investors, taxpayers, and service users.